Preparative‐Scale Biocatalytic Oxygenation of N‐Heterocycles with a Lyophilized Peroxygenase Catalyst. Issue 5 (22nd December 2022) - Pogrányi, Balázs; Mielke, Tamara; Díaz‐Rodríguez, Alba; Cartwright, Jared; Unsworth, William P.; Grogan, Gideon
Abstract: A lyophilized preparation of an unspecific peroxygenase variant from Agrocybe aegerita (r Aae UPO‐PaDa‐I‐H) is a highly effective catalyst for the oxygenation of a diverse range of N ‐heterocyclic compounds. Scalable biocatalytic oxygenations (27 preparative examples, ca. 100 mg scale) have been developed across a wide range of substrates, including alkyl pyridines, bicyclic N ‐heterocycles and indoles. H2 O2 is the only stoichiometric oxidant needed, without auxiliary electron transport proteins, which is key to the practicality of the method. Reaction outcomes can be altered depending on whether hydrogen peroxide was delivered by syringe pump or through in situ generation using an alcohol oxidase from Pichia pastoris ( Pp AOX) and methanol as a co‐substrate. Good synthetic yields (up to 84 %), regioselectivity and enantioselectivity (up to 99 % ee ) were observed in some cases, highlighting the promise of UPOs as practical, versatile and scalable oxygenation biocatalysts. Abstract : A lyophilized preparation of an unspecific peroxygenase variant from Agrocybe aegerita (r Aae UPO‐PaDa‐I‐H) is a highly effective catalyst for the oxygenation of a diverse range of N ‐heterocyclic compounds. Scalable, high yielding and enantioselective biocatalytic oxygenations have been developed, including 27 preparative examples (ca. 100 mg scale) across a wide range of substrates, including alkyl pyridines, bicyclic N ‐heterocycles and indoles.